SARS-CoV-2 induced hepatic injuries and liver complications - Saeed, Umar; Piracha, Zahra Zahid; Uppal, Sara Rizwan; Waheed, Yasir; Uppal, Rizwan (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which is resilient, highly pathogenic, and rapidly transmissible. The COVID-19 patients have been reported to have underlying chronic liver abnormalities linked to hepatic dysfunction. Main Body: Viral RNAs are detectable in fecal samples by RT-PCR even after negative respiratory samples, which suggest that SARS-CoV-2 can affect gastrointestinal tract and the liver. The case fatality rates are higher among elderly and underlying comorbidities such as hypertension, diabetes, liver abnormality, and heart disease. There is insufficient research on signaling pathways. Identification of molecular mechanisms involved in SARS-CoV-2 induced damages to hepatocytes is challenging. Herein we demonstrated multifactorial effects of SARS-CoV-2 on liver injury such as psychological stress, immunopathogenesis, systemic inflammation, ischemia and hypoxia, drug toxicity, antibody dependent enhancement (ADE) of infection and several others which can significantly damage liver. Conclusion: During COVID-19 pandemic, it is necessary for clinicians across the globe, to pay attention to SARS-CoV-2 mediated liver injury, to manage the rising burden of hepatocellular carcinoma. To face the challenges during the resumption of clinical services for patients with pre-existing liver abnormalities and HCC, the impact of SARS-CoV-2 on hepatocytes should be investigated both in vitro and in vivo.